Lignin at nanoscale dimensions - Maia, Rosangela Almeida [UNESP]; Goncalves, Adilson Roberto [UNESP] (Springer Nature, 2024)
There is a constant search to build a more sustainable world, with the replacement of petroleum-based materials, and the development and advancement of various scientific fields. Polymers derived from lignocellulosic biomass have been considered a suitable alternative to replace petroleum-based materials due to their wide availability, properties, low cost, and ecological footprint. However, it is worth highlighting that there are some challenges faced with the use of polymers based on plant, including lack of performance, durability, economic incentives, and efficient approaches to processing and valorizing biomass. In this context, nanotechnology and nanoscience have been a breakthrough to overcome these issues faced in the production of polymers based on plants and the valorization of biomass. The use of nanotechnology allows the development of nanopolymers and nanocomposites with advantageous and unique properties, paving the way for sustainable materials. At present, research on lignin nanoparticles (LNPs) has gained an increased interest in the valorization of lignin. Therefore, this chapter is focused on the properties, synthesis and methods, and preparation of lignin nanoparticles, as well as their application in different fields.
Keywords: Applications; Lignin; Nanoparticles; Properties